COMPARISON OF NUTRITIONAL AND PROTEASE ACTIVITY PROFILES OF TWO LIVE FEED CANDIDATES OF Pseudodiaptomus SPECIES - Rina Puji Astuti; Alim Isnansetyo; Rarastoeti Pratiwi; Suwarno Hadisusanto (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2022)
Pseudodiaptomus species are one of the copepods species as a superior live feed to date due to their nutrition and digestive enzyme contents. Some of them have been used as natural for rearing marine fish larvae. The purposes of this study were to compare the nutritional and protease activity between two species of Pseudodiaptomus originated from Indonesian waters, and to determine more superior species to cultivate. Two different feeds i.e. Thalassiosira sp. and milk powder were used to grow the Pseudodiaptomus species. Analysis of amino acids (AAs) and fatty acids (FAs) profiles were carried out for both the Pseudodiaptomus species samples and the feeds, while the protease activity assay was carried out only for the Pseudodiaptomus species samples. Results indicated that the nutritional and protease activity profiles of Pseudodiaptomus were affected by the types of feed. Pseudodiaptomus code P61 was more superior to Pseudodiaptomus code P71. This code P61 species contained a wide variety of essential fatty acids and exhibited stabile protease activity under the different feeding treatments. However, P61 contained a lower total AA content than P71. Both of them could be cultivated because they were complementary in nutrients to each other.